2011
DOI: 10.1088/0953-2048/24/7/075005
|View full text |Cite
|
Sign up to set email alerts
|

The temperature dependence of the resistivity in Ba1 −xKxFe2As2superconductors

Abstract: The temperature dependence of the resistivity ρ(T ) of 122-Fe-pnictides is studied. The normal state resistivity ρ n (T ) is analyzed with the scaling method. It is found that the ρ n (T ) data can be scaled onto the universal curves for optimal, overdoped and underdoped samples, by using the energy scale , the resistivity ρ and the residual resistivity ρ 0 as the scaling parameters, where the universal curves can be described by an exponential function. The overall resistivity can be described by a uniform fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
(48 reference statements)
1
21
0
Order By: Relevance
“…This is a surprising result: a metal with such a small Fermi-energy can't be considered a degenerate-Fermi gas even at room temperature. This is expected to lead to a non-trivial temperature dependence of various transport properties, as indeed was found for example for the Seebeck coefficient [17] and Hall resistivity [18]. When we lower the temperature below T c , we find surprising results.…”
supporting
confidence: 63%
“…This is a surprising result: a metal with such a small Fermi-energy can't be considered a degenerate-Fermi gas even at room temperature. This is expected to lead to a non-trivial temperature dependence of various transport properties, as indeed was found for example for the Seebeck coefficient [17] and Hall resistivity [18]. When we lower the temperature below T c , we find surprising results.…”
supporting
confidence: 63%
“…[25][26][27][28][29][30][31] It is expected that fluctuation effects around the superconducting transition may also present differences in these two types of iron pnictides. 32 These effects have been already investigated in presence of charge-doping, [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] but to our knowledge still remain unexplored in isovalently substituted iron-pnictides.…”
Section: Introductionmentioning
confidence: 99%
“…20 Very recently, it has been reported that the overall resistivity for optimal, overdoped and underdoped Ba 1−x K 0.4 Fe 2 As 2 samples can be also described by a uniform formula taking into account the 3D fluctuation contribution. 21 Nevertheless, we would like to notice that the experimental data used in this case are taken from the literature, and the analysis is performed in the absence of the magnetic field. The results here discussed have been obtained for high quality single crystals, and in the presence of an external magnetic field up to 14.…”
Section: Introductionmentioning
confidence: 99%